Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
This Selected Issues paper analyzes the use of fiscal rules in Poland and also suggests improvements. The study reviews the income tax reforms, developments in the polish tax system, and discusses the need and scope for public expenditure reform, employment, and the role of reforms of labor market institutions in reducing the unemployment rate. The paper highlights the trend in the saving-investment balance, the major determinants of private saving, and presents the results of a simple econometric analysis based on a panel dataset of selected transition economies.